IT-aggregators of tourism products in the structure of the tourism services market - Chaika, Tatiana (International Science Group, 2024)
The study focuses on the functional features of IT-aggregators of tourism products. Due to the development of computer technology, the role of offline travel agencies is significantly reduced, and the functions of travel agents are partially transferred to various online platforms that are aggregators of travel offers. At the same time, the request for personal involvement is a significant characteristic of the tourism and hospitality industry. Therefore, the development of computer technologies does not lead to a complete rejection of off-line travel agencies. IT-aggregators of tourism products are an effective tool of interaction between tour operators, travel agencies, and customers.

У цьому дослідженні акцент робиться на вивчення функціональних особливостей IT-агрегаторів туристичних продуктів. З розвитком комп'ютерних технологій роль офф-лайн турагентів істотно знижується, а турагентські функції частково переходять до різних онлайн-платформ, що є агрегаторами туристичних пропозицій. Разом з тим, запит на особистісну участь є значущою рисою індустрії туризму та гостинності. Тому розвиток комп'ютерних технологій не призводить до повної відмови від послуг оф-лайн турагентів. IT-агрегатори туристичних продуктів – ефективний інструмент взаємодії туроператорів, турагентів та клієнтів.
IT-агрегатори туристичних продуктів у структурі ринку туристичних послуг
Keywords: tourism services market; IT-aggregator; tourism product; tour operator; travel agent; ринок туристичних послуг; ІТ-агрегатор; туристичний продукт; туроператор; турагент